2016
DOI: 10.1111/mec.13659
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptomic response of the coral Acropora digitifera to a competent Symbiodinium strain: the symbiosome as an arrested early phagosome

Abstract: Despite the ecological significance of the relationship between reef-building corals and intracellular photosynthetic dinoflagellates of the genus Symbiodinium, very little is known about the molecular mechanisms involved in its establishment. Indeed, microarray-based analyses point to the conclusion that host gene expression is largely or completely unresponsive during the establishment of symbiosis with a competent strain of Symbiodinium. In this study, the use of Illumina RNA-Seq technology allowed detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
144
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(155 citation statements)
references
References 57 publications
9
144
2
Order By: Relevance
“…However, a few experiments investigated differential gene expression in coral larvae with and without symbionts, all of which reported the absence of or rather small gene expression differences in the transcriptomes of symbiotic hosts when compared to the aposymbiotic state (deBoer et al, 2007;Voolstra et al, 2009b;Schnitzler and Weis, 2010). Only recently, a study by Mohamed et al (2016) detected a transient period of differential expression involving a limited number of genes (3% of assayed transcriptome) 4 h after the exposure of Acropora digitifera planula larvae to a competent strain of Symbiodinium. While yet to be applied for larval studies, symbiosis-specific genes have been identified recently in Aiptasia anemones (Bucher et al, 2016;Wolfowicz et al, 2016).…”
Section: Biochemical and Molecular Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few experiments investigated differential gene expression in coral larvae with and without symbionts, all of which reported the absence of or rather small gene expression differences in the transcriptomes of symbiotic hosts when compared to the aposymbiotic state (deBoer et al, 2007;Voolstra et al, 2009b;Schnitzler and Weis, 2010). Only recently, a study by Mohamed et al (2016) detected a transient period of differential expression involving a limited number of genes (3% of assayed transcriptome) 4 h after the exposure of Acropora digitifera planula larvae to a competent strain of Symbiodinium. While yet to be applied for larval studies, symbiosis-specific genes have been identified recently in Aiptasia anemones (Bucher et al, 2016;Wolfowicz et al, 2016).…”
Section: Biochemical and Molecular Relationshipmentioning
confidence: 99%
“…Especially considering reports that some larvae may digest the symbionts instead of engaging in a symbiotic relationship (Titlyanov et al, 1998;Mies et al, 2017c). The available gene expression studies are inconclusive in regard to whether the observed gene expression changes in coral larvae are specific to the symbiont exposure (deBoer et al, 2007;Voolstra et al, 2009a;Schnitzler and Weis, 2010;Mohamed et al, 2016). For instance, it is unclear if these changes are related to a mutualistic relationship or to the mere presence of a foreign algal body.…”
Section: Is There a Mutualism From The Start?mentioning
confidence: 99%
“…A key antioxidant in the oxidative stress response in symbiotic cnidarians turns out to be glutathione (Sunagawa et al, 2009; Meyer and Weis, 2012). The gene encoding glutathione S-transferase was previously observed to be downregulated in corals, sea anemones, different strains of green hydra and Paramecium (Kodama et al, 2014; Lehnert et al, 2014; Ishikawa et al, 2016; Mohamed et al, 2016). Our study supports this view (Table 1) and may point to a conserved feature of oxidative stress response in algal-animal symbiosis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that during establishment of coral–algal symbiosis the host immune response may be partially suppressed (Weis et al, 2008; Mohamed et al, 2016). Our observations in Hydra together with previous findings in corals indicate that regulation of symbiosis by innate immunity pathways indeed may be a general feature of cnidarian symbiosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation